ULTIMATUM TO NEO IMPERIALISM; ECOCRITICISM IN KHAIRANI BAROKKA POEM ‘ULTIMATUM ORANGUTAN’ - Sumbayak, Desri Maria (Annual International Conferences on Language, Literature, and Media, 2022)
The article discusses issues of ecology injustices in a single poem Ultimatum Orangutan  written by Khairani Barokka in 2021. The poetry is taken from her second poetry collection entitled the same Ultimatum Orangutan which is shortlisted  for Barbellion Prize. The study employs ecocriticism frameworks in literary works and uses a qualitative-interpretative method. The words, phrases, and lines are observed, connected, inferred, and concluded based on the subthemes of the discussion. The study results in two parts. Firstly, the forms of neo-imperialism exploitation of lands are conveyed through foreign imperialists such as big industrial companies based in Indonesia, and the movie and play game industry. The form also shows the authority in Indonesia that always supports capitalism. Secondly, the neo-imperialisms addressed in the poem include the extinction of orangutans, the death of people, and the loss of land in Indonesia. This study reflects that the literature could function to challenge the issues of climate justice in very provocative ways.